In Search for a Credit Crunch in Germany - Torsten Schmidt; Lina Zwick (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
The purpose of this paper is to investigate whether a credit crunch occurred in Germany during the recent financial crisis and to analyze the underlying factors. In order to disentangle credit supply and demand we specify a theory-based dynamic disequilibrium model of the German credit market. To estimate this model we use a new approach based on Bayesian Inference suggested by Bauwens and Lubrano (2007). Besides the analysis of the whole banking sector we will apply the model to five groups of banks (big private banks, Landesbanken, savings banks, credit cooperatives, regional institutions of credit cooperatives) that were affected differently by the financial crisis. The results suggest that a credit crunch did not occur in Germany during the recent economic crisis as well as during the following recovery starting in 2010. Furthermore, we find that especially those banks that were more affected by the financial crisis through huge impairments restricted their credit supply more than others. Both supply and demand side factors contributed to the stabilization of credit financing. This suggests that the structure of the German banking sector as well as economic policy measures avoided a credit crunch.
Keywords: C32; E51; G21; 330; Credit Crunch; Bank Lending; Financial Crisis